Enhanced mid-visible light absorption and long-lived charge carriers in an electronically and structurally integrated BiVO4-TiO2 photoanode for efficient artificial photosynthesis applications - Jha, Vikas Kumar; Salgaonkar, Kranti N.; Saha, Avishek; Gopinath, Chinnakonda S.; Iyer, E. Siva Subramaniam (Nanoscale, 2025)
The ever-increasing demand for sustainable solutions for eliminating environmental pollutants, solar energy harvesting, water splitting, etc. have led to the design and development of novel materials to achieve the desired result. In this regard, structurally and electronically integrated (SEI) BiVO4-TiO2 (SEI-BVT) with abundant heterojunctions has emerged as a promising entity for efficient charge separation, which in turn enhances artificial photosynthesis (APS) activity. The present work adopted a unique synthetic strategy using SILAR to fabricate SEI-BVT from ionic precursors (Bi3+ and VO43-) into the pores of TiO2, exhibiting benchmark APS efficiency compared to the individual components. This preparation results in approximately 180 trillion uniformly distributed heterojunctions in 1 mg cm-2 of the SEI-BVT photoanode material. Charge carriers in SEI-BVT and BiVO4 are similar; however, the recombination is highly hindered when SEI-BVT heterojunctions are formed in the former. Our earlier work demonstrated 31-38% solar-to-fuel efficiency (STFE) with BiVO4-TiO2 for APS in the presence of the Pd-nanocube co-catalyst. The emphasis of the current work is to explore the dynamics of the light-induced processes in these heterojunctions to understand the interfacial charge transfer process. Femtosecond transient absorption (TA) spectroscopy has been employed to monitor the excited state dynamics. Our results show that new trap states have evolved under light illumination, which are significantly long-lived and hinder charge recombination, and consequently enhance STFE. A significantly large number of charge carriers exhibit a lifetime of >> 6 ns with visible light photons, at least up to 720 nm, which is higher than the band-gap absorption onset at 490 nm for SEI-BVT compared to bulk BiVO4. The rate of formation of charge carriers is significantly affected in the heterojunctions.